1919
DOI: 10.1086/279706
|View full text |Cite
|
Sign up to set email alerts
|

Gigantism in Nicotiana tabacum and Its Alternative Inheritance

Abstract: WITHIN recent years observers working with different varieties of Nicotiana tabacum grown commercially in the United States and elsewhere have recorded the sudden appearance of occasional giant plants of abnormally high leaf number. Except in height and number of leaves, which may be increased several times above the usual number, these giant plants in general appearance do not depart widely from the varietal type from which they took their origin. The great increase in number of leaves, together with a greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1961
1961
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Florigen-like systemic signals are expected to substitute for different environmental stimuli in diverse plant species. In a seminal discovery, Garner and Allard (26,27) identified a recessive mutation in the Maryland Mammoth (MM) tobacco strain that confers a short-day response on day-neutral tobacco plants. When grown under long days, cv.…”
Section: Systemic Sft Signals Substitute For Short-and Long-day Flowementioning
confidence: 99%
“…Florigen-like systemic signals are expected to substitute for different environmental stimuli in diverse plant species. In a seminal discovery, Garner and Allard (26,27) identified a recessive mutation in the Maryland Mammoth (MM) tobacco strain that confers a short-day response on day-neutral tobacco plants. When grown under long days, cv.…”
Section: Systemic Sft Signals Substitute For Short-and Long-day Flowementioning
confidence: 99%
“…Genetic analyses have revealed that single gene differences can alter the flowering response type; for example, mutations that introduce or eliminate an effect of photoperiod Current address: Department of Horticulture, 1575 Linden Drive, University of Wisconsin, Madison, WI 53706-1590. * To whom correspondence should be addressed. on flowering have been described in tobacco (Allard, 1919), maize (Galinat and Naylor, 1951), pea (Murfet, 1989), sorghum (Quinby and Karper, 1945), and Arabidopsis (Rbdei, 1962;Koornneef et al, 1991;Zagotta et al, 1992). A mutation in gibberellin biosynthesis has recently been shown to inhibit the ability of Arabidopsis to flower in noninductive photoperiods (Wilson et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridizations were subsequently performed to identify more precisely the tissue in which steady state NFL transcripts accumulated. The short day-requiring cultivar N. tabacum cv Maryland Mammoth (Allard, 1919;Gebhardt and McDaniel, 1987) was used to control the developmental state of the plants from which shoot apices were harvested. Under the growth chamber conditions used, nine inductive short-day cycles are necessary and sufficient to induce flowering.…”
mentioning
confidence: 99%